Non-contact acoustic capture of microparticles from small plasma volumes. Issue 12 (21st June 2015) - Evander, Mikael; Gidlöf, Olof; Olde, Björn; Erlinge, David; Laurell, Thomas
<x xml:space="preserve">Abstract</x> An acoustic non-contact method for extracting platelet-derived microparticles from small plasma volumes is presented. The method has higher recovery and can handle smaller sample volumes than conventional differential centrifugation method. It is optimal for the analysis of precious biobank samples with limited volume.